The estimation of cost effectiveness of the composite restoration - Abdul Majeed, Kais Raad; Choon, LC (2014)
The purpose of this study is to evaluate the cost effectiveness of posterior composite resin through the amount of microleakage. Materials and Methods: 72 Cl V cavities were prepared in 36 teeth (extracted upper first premolar), one buccally and one palatally in each tooth, the cavities were located in the middle third of the crown. The teeth were randomly divided into three groups (24 cavities for each group); Group A: filled with Helio- molar radiopaque composite. Group B: filled with Tetricceram composite. Group C: filled with an Ariston PHc composite . After the teeth were filled, they were restored in normal physiological saline in an incubator at 37 oC. one third of each group (8 cavities) were thermocycled for one day (30 cycle), 2nd third thermocycled for 10 days (300 cycle), and the last third thermocycled for 100 days (3000 cycle). One-way-ANOVA-analysis revealed significant differences among the groups (p<0.05) in the terms of the cost effectiveness, The results revealed that the Ariston Phc composite has better cost effectiveness from the other tested types. It is not a significant difference between Group C and B, and it is a significant difference between Group C and A. Material C has better cost effective than other tested materials. None of the materials tested was able to achieve the absolute cost effectiveness.